Capnoperitoneum During Peroral Endoscopic Myotomy—Recognition and Management: A Case Report. Issue 6 (15th March 2017) - Lee, Eric; Brodsky, Jay B.; Rivas, Homero; Zheng, Karl; Brock-Utne, John G.
Abstract : Peroral endoscopic myotomy (POEM) is a minimally invasive procedure for treating esophageal achalasia. During POEM, carbon dioxide is insufflated under pressure into the esophagus and stomach, which can cause clinically significant capnoperitoneum, capnomediastinum, or capnothorax. We present a case in which gas accumulation in the abdomen during POEM had adverse effects on ventilation. Once the cause was recognized, needle decompression of the abdomen led to immediate improvement in ventilation.